Customized cooking method improves total antioxidant activity in selected vegetables - Ng, Z.X.; Chai, J.W.; Kuppusamy, U.R. (2011)
The present study compares water-soluble phenolic content (WPC) and antioxidant activities in Chinese long bean (Vigna unguiculata), bitter gourd (Momordica charantia), water convolvulus (Ipomoea aquatica) and broccoli (Brassica olearacea) prior to and after subjecting to boiling, microwaving and pressure cooking. The total antioxidant activity was increased in cooked water convolvulus, broccoli and bitter gourd, estimated based on the ferric reducing antioxidant power, the Trolox equivalent antioxidant capacity and 2,2-diphenyl-1-picryl-hydrazyl radical scavenging activity. Pressure cooking did not cause any significant decline in the antioxidant property. Boiling generally improved the overall antioxidant activity in all the vegetables. Correlation analysis suggests that WPC contributed to significant antioxidant activities in these vegetables. Thus, prudence in selecting an appropriate cooking method for different vegetables may improve or preserve their nutritional value.